Risk factors of adverse drug reactions of first-line antiretroviral therapy in HIV patients at RSUD Dr. Moewardi - Ana Amalia; Fita Rahmawati (Universitas Ahmad Dahlan, 2020)
Acquired Immuno Deficiency Syndrome (AIDS) is an infection caused by the Human Immunodeficiency Virus (HIV). The antiretrovirals (ARVs) combination is the basis for the management of therapy in HIV/AIDS patients, but it often raises problems like adverse drug reactions (ADRs). This study was conducted to determine the risk factors for the occurrence of ADRs in the use of first-line ARVs. It employed a cross-sectional design with retrospective data collection in patients visiting the Voluntary Cell Counting (VCT) room of RSUD Dr. Moewardi in November-December 2018. The data collected were sociodemographic, behavioral, and clinical characteristics, laboratory test results, and ARV profiles. Findings show that the risk factors for ADRs in the use of first-line ARVs are CD4 of <200 and 0-24 months of taking ARVs.